Developing a Pesantren Community- Based Waste Management and Sanitation Module - Albert Albert; Yunhendri Danhas; Irwandi Irwandi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The low skill level of Management Groups (MGs) responsible for community-based waste management and sanitation facilities in pesantren in Padangpanjang City underpins this study. This issue is associated with the inadequacy of existing training modules. This study aims to develop a valid, practical, and effective module for managing community-based waste and sanitation facilities in pesantren contexts. This research adopts a research and development approach using the ADDIE model. The participants were 35 MG members from pesantren in Padangpanjang, West Sumatra. Data were collected through interviews, observations, and questionnaires, and analyzed using qualitative and quantitative methods. The findings reveal that existing modules lack essential components and do not adequately address environmental management knowledge. The developed module demonstrates high validity (0.86) and practicality (K = 0.87), and significantly improves participants’ knowledge (p < 0.05). In conclusion, the module is empirically validated as valid, practical, and effective. It provides a structured learning resource to support capacity building among MGs and enhances the effectiveness of facilitator-led training. This study contributes to strengthening community-based environmental management practices in pesantren and supports sustainable development efforts.